Breastfeeding and Complementary Feeding Practices among Caregivers at Seshego Zone 4 Clinic in Limpopo Province, South Africa - M. H. Mphasha; M. S. Makwela; N. Muleka; B. Maanaso; M. M. Phoku (MDPI AG, 2023)
Breastfeeding and complementary feeding are key components of infant and young child feeding that ensure healthy growth, survival, and development. Initiating breastfeeding within an hour after delivery, exclusively breastfeeding for six months, and introducing complementary feeding at six months while continuing breastfeeding up to 24 months or beyond, helps in the prevention of malnutrition, which is a public health problem. The aim of this study was to determine breastfeeding and complementary feeding practices among caregivers of children under 24 months in Seshego, Limpopo Province. A quantitative and cross-sectional design was applied to collect data from 86 caregivers using convenience sampling. A structured questionnaire was utilised to gather data and analysed through statistical software, using descriptive and inferential statistics. Chi-square tests were used to determine associations at a 95% confidence interval where a p-value of <0.05 was considered statistically significant. The findings show that 55% of participants had good breastfeeding and complementary feeding practices. Moreover, 94.2% of participants breastfeed within an hour after delivery at a healthcare facility. Only 43.6% of children were exclusively breastfed. Most participants (52.3%) gave children food before six months and 45.1% introduced complementary feeding at the appropriate age. Also, 69.7% of children across all age groups were not given infant formula. No statistical association was observed between feeding practices and sociodemographic. Breastfeeding was initiated within an hour after delivery at the healthcare facilities, however, post discharge exclusive breastfeeding maintenance remains a challenge. Few infants were introduced to complementary feeding at the appropriate age. A post discharge intervention to practice exclusive breastfeeding, continued breastfeeding, and introduction of appropriate complementary feeding is recommended.